Control Strategies of a Three-Phase Wireless Power Transfer Charger - El Ancary Marouane; Lassioui Abdellah; El Fadil Hassan; Bouanou Tasnime; El Idrissi Zakariae; Yahya Abdelhafid; Hasni Anwar; Asri Yassine El (EPJ Web of Conferences, 2025)
To maintain the required power output and guarantee optimal efficiency, voltage, and current control are essential in Wireless Power Transfer (WPT) systems. Closed-loop feedback mechanisms are commonly employed to regulate the voltage and current of the Battery Electric Vehicle (BEV) in different charging modes. This paper presents the design of controllers for multiple control strategies implemented in a three-phase WPT charger for a BEV. First, the fundamental principles of the WPT system are given with the equivalent three-phase WPT circuit. Then, the control strategies are presented to control the current in the Constant Current-Constant Voltage (CC-CV) charging mode and in the Multi-stage Current Method (MCM) charging mode. Finally, simulation results demonstrate that these control strategies are robust and precise across various BEV charging types.